2007
DOI: 10.1007/s10654-007-9194-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of recruiting a birth cohort through the Internet: the experience of the NINFEA cohort

Abstract: The NINFEA cohort is an Italian birth cohort aiming at recruiting pregnant women through the Internet and following-up their children. To understand whether Internet-based recruitment was feasible we started a pilot in July 2005 targeted to pregnant women visiting the hospitals of the city of Turin (900,000 inhabitants), where we advertised the study. For this purpose we constructed a website (www.progettoninfea.it), with on-line questionnaires to be completed during pregnancy and at 6 and 18 months after deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 25 publications
(25 reference statements)
3
86
0
Order By: Relevance
“…Study population NINFEA (Nascita e Infanzia: gli Effetti dell'Ambiente; Birth and Childhood: Effects of the Environment) is an ongoing Italian internet-based birth cohort established in 2005 (www.progettoninfea.it) [23]. Members of the cohort are children of mothers who have access to the internet and enough knowledge of Italian to complete online questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Study population NINFEA (Nascita e Infanzia: gli Effetti dell'Ambiente; Birth and Childhood: Effects of the Environment) is an ongoing Italian internet-based birth cohort established in 2005 (www.progettoninfea.it) [23]. Members of the cohort are children of mothers who have access to the internet and enough knowledge of Italian to complete online questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…New methods for contacting participants, which have been used in other more recently started studies, including use of internet, sms and e-mail, are currently being explored [92, [252][253][254][255][256][257][258][259][260][261][262].…”
Section: Follow Up and Retention Strategiesmentioning
confidence: 99%
“…The Lifeways study was one of the first to show that general practitioner-reported wheeze or asthma (52) Czech Republic 7577 1994 x Devereux et al (53) UK 1400 1997 x x Drouillet et al (54) France 1900 2003 x x x x Dubois et al (55) Canada 1450 1998 x x Eggesbo et al (56) Norway 2500 2003 x x x Emanuel et al (57) UK 3076 1958 x Gorden-Larsen et al (58) USA 14 706 1995 x Gracie et al (59) Canada 3388 2008 x x Grandjean et al (60) Faroe Islands 1022 1986 x x x x Guldner et al (61) France 4000 2002 x x Guxens et al (62) Spain 3768 1997 x x x x x Grazuleviciene et al (63) Lithuania 4405 2007 x Hawkes et al (64) Ireland 2185 2008 x Hawkins et al (65) UK 13 113 2000 x Hill et al (66) Wales 420 2009 x x Hryhorczuk et al (67) Ukraine 4510 1992 x x x Hui et al (68) Hong Kong 8327 1997 x x Hunt et al (69) Canada 521 1981 x x Inskip et al (70) UK 3159 1998 x x Jaddoe et al (71) Netherlands 10 000 2002 x Jedrychowski et al (72) Poland 432 2000 x x Kaplowitz et al (73) UK 224 1986 x x Karvonen et al (74) Finland 442 2002 x x x x Katier et al (75) Netherlands 2500 (95) Germany 2000 2011 x x x x Richiardi et al (96) Italy 7500 2005 x x x x Schaefer-Graf et al (97) Germany 324 1995 † x x Sekine et al (98) Japan 8941 1992 x x Skalkidou et al (99) Sweden 580 2009 x x Tsuchiya et al (100) Japan 1260 2007 x x van Eijsden et al (101) The Netherlands 6161 2003 x x x x Vandentorren et al (102) France 20 000 2011 x x x Vecchi Brumatti et al (103) Italy 900 when the child averaged 3 years was inversely associated with maternal fruit and vegetable and fish consumption during pregnancy (1...…”
Section: Dietary Patterns and Risk Of Childhood Wheezing Or Asthmamentioning
confidence: 99%